2020
DOI: 10.1515/nanoph-2020-0375
|View full text |Cite
|
Sign up to set email alerts
|

Active nonlocal metasurfaces

Abstract: Actively tunable and reconfigurable wavefront shaping by optical metasurfaces poses a significant technical challenge often requiring unconventional materials engineering and nanofabrication. Most wavefront-shaping metasurfaces can be considered “local” in that their operation depends on the responses of individual meta-units. In contrast, “nonlocal” metasurfaces function based on the modes supported by many adjacent meta-units, resulting in sharp spectral features but typically no spatial control of the outgo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 37 publications
0
47
0
Order By: Relevance
“…34 We propose a possible fabrication procedure in Sec. S2 in the Supplemental Materials based on extending recent efforts demonstrating single-layer q-BIC metasurfaces, 19,27,28 and we study the influence of misalignment of the two layers in Sec. S3 in the Supplemental Materials, concluding that standard tolerances more than suffice to demonstrate these concepts in the near-infrared.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…34 We propose a possible fabrication procedure in Sec. S2 in the Supplemental Materials based on extending recent efforts demonstrating single-layer q-BIC metasurfaces, 19,27,28 and we study the influence of misalignment of the two layers in Sec. S3 in the Supplemental Materials, concluding that standard tolerances more than suffice to demonstrate these concepts in the near-infrared.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Fano resonant metasurfaces capable of shaping the wavefront of light at resonance have been demonstrated based on the symmetry features of q-BICs. 14,21,[26][27][28] In Ref. 21, it was demonstrated that the orientable linear dichroism afforded by the p2 space group can carry a geometric phase when excited by circular polarization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, this platform was extended to a 2D guided mode resonator, also called a non‐local metasurface. [ 185 ] Dang et al. demonstrated strong coupling between the metasurface and the exciton resonance with a Rabi splitting in the 200 meV range.…”
Section: Strong Light‐matter Interactionsmentioning
confidence: 99%
“…Thanks to the extensive research on stimuli-responsive materials, such as phase-change materials, electro- and magneto-optical materials, and liquid crystals, various active metasurfaces have been reported. 10,19,20 Modulated metasurfaces for tunable absorption, 21 beam steering, 22,23 varifocal metalenses, 24 and ultrafast optical nonlinearity 25 have been demonstrated, holding great potential for applications in tunable photonics. For conventional phase-changing materials based on modification of the refractive index of the substrate or the medium around the plasmonic units, 26–30 it is challenging to obtain large spectral tuning range due to limited refractive-index changes and optical losses.…”
Section: Introductionmentioning
confidence: 99%